Information Technology Investment Strategy Planning: Balance Scorecard Approach - Henny Hendarti; Iwan Kurniawan (CommIT (Communication and Information Technology) Journal, 2011)
Purpose of this research are to prepare the IT investment strategy using Balanced Scorecard approach in the company where the appropriate planning of this IT investment strategy can maximize the competitive benefit in the company, and it also to recommended a strategy of IT investment that can be implemented and measure the rate of return from the IT investment in the company. Research Method used book studies, field studies, and analysis system. Book studies from the books and journal. Field studies done by observation, interview, and questioner, and analysis system done by analyzed the ongoing system in the company. The result from this analysis is a recommendation in investment IT such as sales module, payment module, and report module. Then for the conclusion, this information technology investment planning can be develop to another investment implementation such authorized website of the company and using PDA (Personal Digital Assistant)Index Terms - Planning, Information Technology, Investment, Balance Scorecard